ANTESEDEN DAN OUTCOMES WORK-FAMILY CONFLICT; MENGUJI MODEL HUBUNGAN PEKERJAAN- KELUARGA PADA PEGAWAI BERSEKOLAH DI DAERAH ISTIMEWA YOGYAKARTA (Fokus Ekonomi, 2010)
The purpose of this research is to examine the relationship between antecedent work-family conflict (job stress, job support, family support, family stress), work-family conflict, and outcomes work-family conflict (job satisfaction, performance, affective commitment).  This research also investigates the impact of performance on job satisfaction, performance on affective commitment, and job satisfaction on affective commitment. Variabel in this research were measured via survey of 226 student Magister Management on the University in the DIY.  Structural Equation Modeling (SEM) were used to examine the effect to antecedent and outcomes of work-family conflict. Results showed that the estimate model in this research is acceptable based on the goodness fit index. The structural relationship showed that job stress, family support, and family stress significantly related to work-family conflict, but no significantly related with family support. Work-family conflict significantly related to performance and job satisfaction, but not to affective commitment. It also showed that job satisfaction significantly related to affective commitment and performance; performance to affective commitment. Finally, these results have an important implication to managers in scheme work-family orient.